The Satisfaction of Using the Service of Wireless Computer Network Case Study: Nakhon Si Thammarat Municipality - Pakorn, Wachirasak (International Journal of Multidisciplinary in Management and Tourism, 2020)
The research objectives were to study the satisfaction level of using the service of wireless computer network: Nakhon Si Thammarat municipality as the case study. It was the survey research. The samples were students, undergraduates, state enterprise officers, private employees, and people living in Nakhon Si Thammarat municipality, total of 400 units which were derived from the table of Taro Yamane. The research tool was the close-ended questionnaire which its content validity was reviewed by three experts and was shown the Index of Item-Objective Congruence (IOC) of 0.95. The data analysis applied the statistics of frequency, percentage, mean, standard deviation; and the method of content analysis. The research findings were as follows: (1) Satisfaction in overall 4 aspects were rated at the high level (= 3.88). When considered in each aspect, the satisfaction was rated at the high level “Speed of Using Network Service” (= 4.01); “Convenience of Using Network Service” (= 3.90);“Stability of Using Network Service” ( = 3.80); and “Security of Using the Network Service” ( = 3.70). Such research findings were beneficially implement to improve the effectiveness of the wireless computer network of Nakhon Si Thammarat municipality.